Reinterpretasi Kisah Abigail dari Perspektif Pairan Dapo’ di Mamasa Sulawesi Barat - Saputra, Jefri Andri; Yunita, Wiwin; Tanan, Rina Lestari; Payung, Yumita Selvi Rombe (Jurnal Teologi Pambelum, 2024)
This study aims to respond to stereotypes and discrimination experienced by women who work as housewives. The author responds to this problem by reinterpreting the story of Abigail in 1 Samuel 25:2-44. The research method in this paper uses the seeing-through approach. The perspective lens used is the pairan dapo’ concept in Mamasa, West Sulawesi. The author finds that the text of 1 Samuel 25:2-44 describes Abigail as a housewife who does not just stay home and always submits to her husband's orders and decisions. Abigail has the space and role to criticize Nabal's wrong attitudes and actions. Abigail's actions become reflective material for constructing that housewife can play a role in seeking the welfare of their families. This role does not lie in an economic role, but rather wisdom and knowledge of ethical values to criticize her husband and family.